A Portrait of Basic Laboratory Skills among Grade XII Students at SMAN 1 Rasau Jaya - Nurhasanah, Siti; Candramila, Wolly; Mardiyyaningsih, Asriah Nurdini (Unnes Science Education Journal, 2024)
School laboratories are vital for building students' understanding and scientific skills through hands-on activities. However, the laboratory at SMAN 1 Rasau Jaya in Kubu Raya Regency is underutilized, potentially reducing students' motivation and skills. This study aims to evaluate the basic laboratory knowledge and skills of students at SMAN 1 Rasau Jaya, focusing on measurement, weighing, and dilution. This research utilizes a descriptive quantitative survey method to assess the basic laboratory knowledge and skills of Grade XII science students at SMAN 1 Rasau Jaya, with a purposive sample of 35 students. Data analysis was conducted to describe laboratory knowledge and skills as well as their relationship. The study found students’ laboratory knowledge to be generally moderate, with average scores of 41% for measurement, 45% for weighing, and 43% for dilution skills. Practically, 34.3% of students were rated as good and 8.6% as very good in measurement skills. Weighing skills were stronger, with 68.6% in the very good category, while dilution skills need improvement, with only 31.4% very good and 17.1% moderate. A low but significant correlation (r = 0.376, p = 0.026) suggests that theoretical knowledge hasn't fully translated into practical ability. In conclusion, the study highlights a gap between students' theoretical knowledge and practical skills, suggesting a need for increased hands-on practice to enhance scientific proficiency and motivation among students at SMAN 1 Rasau Jaya.